Istotne róznice w ocenie magnezurii mierzonej bezposrednio i wyliczonej ze stosunku Mg+2 / kreatynina u maratonczyków - Ratkowski, W.; Matuszkiewicz, A.; Kaczor, J. J.; Popinigis, J. (Sport wyczynowy, 2002)
Background. Aim of this work was to compare results of two methods which can be employed in assessment of magnesuria. The first one was the direct method, in which magnesium content was measured in urine which had been collected for quite long period of the time, and the second, the indirect method, which was based on calculation on magnesium excretion per g of creatinine. Material and methods. The urine was collected before and after marathon run performed by two runners. The volume of urine was measured and the rate of magnesium excretion with urine was calculated and expressed as micromoles per hr (the direct method). In the same samples creatinine content was also measured and the output of this substance into urine was expressed in g per hr (the indirect method) The absolute values of magnesuria (in micromoles per hr) was compared, using the same urine samples, with the results obtained on a basis of magnesium / creatinine ratio. Results. Assuming the initial, resting output as 100%, in case of runner No1, the rate of magnesuria was 47% during the first 10 hr after the run, and 167% after 25 hr. In the same samples the rate of magnesuria calculated from Mg+2 / creatinine ratio was 30% after 10 hr and 68% after 25 hr. In case of runner No 2 the rate of magnesuria was measured in urine collected during the period 0-5 hr and 0-21 hr after the run. According to direct measurements the rate was 37 % and 317% after 5 and 21 hr respectively, whereas when calculated from Mg+2 / creatinine, the results were 19% and 217%. Conclusion. Due to inconvenience of the collection method it is much easier to check the concentration of magnesium (or other urine constituents) in small urine samples, and then to calculate the output into urine per g of excreted creatinine. Our results indicate however that this indirect method is less accurate, and therefore, the preference should be given to direct measurements, performed with urine which should be carefully collected during quite long period before and after the exercise.